Using plasmonic excitation to enhance electrocatalytic processes - Germano, Lucas Dias (2024)
There is currently a demand for new technologies and optimization of alternative processes for the generation and conversion of electrical energy to the detriment of the use of fossil fuels. One of the alternatives being studied is the use of light incidence to enhance electrochemical processes. This thesis investigates the impact of plasmonic excitation on electrochemical reactions, building upon the influence of plasmonic relaxation mechanisms. It focuses on two distinct anodic processes: part I - electrosynthesis of water-soluble epoxide from olefin electrooxidation (sulfonated derived styrene), and part II - oxygen evolution reaction (OER) using different electrolytes. While all three main mechanisms of non-radiative plasmonic relaxation (hot-carrier generation, near-field enhancement, and heat generation) occur almost simultaneously, the study demonstrates that careful system design can modulate their relative contribution. The proximity of gold nanoparticles (Au NPs) to reaction intermediates on the electrocatalyst surface significantly affects all mechanisms. The Au NPs act as light harvesters, capturing light and influencing how the resulting energy is utilized. Thus, part I focuses on hot-carrier generation and transfer to nearby molecules as the primary reaction pathway for the epoxide synthesis, which emphasis is due to boost of oxygen generation and the consumption of olefin molecules near the plasmonic centers due to the strong affinity between the sulfonated molecules and the gold atoms. However, the contribution of near-field enhancement (mainly influencing optical properties) and heat generation to the overall reaction kinetics cannot be entirely ruled out. In the other hand, part II investigates the effects of plasmon-induced heating on the solvation shell of electrolyte cations during OER. The thermal effect results in the expulsion of water molecules from the Li+ solvation shell, leading to a configuration resembling that of a Cs+ and potentially mimicking its electrochemical behavior. However, again, the contributions from the near-field enhancement and hot-carrier generation cannot be entirely ruled out. The latter mechanism, though shortlived, may still play a role in this case. As a recurring theme throughout the scientific literature and reinforced by this thesis, a powerful synergy exists between plasmonic excitation and electrochemistry. This combination offers a versatile tool for driving, enhancing, probing, and synthesizing diverse chemical reactions and species. The implications for the energy field are particularly remarkable. By manipulating the photo-perturbed electric current, which can potentially amplify or alter reaction mechanisms, can lead to breakthroughs in energy research. This paves the way for the development of more efficient and sustainable energy conversion technologies.